Establishing an algorithm for molecular genetic diagnostics in Chinese children with brachydactyly type E - Wang, Xueqian; Guan, Shengzhuang; Gao, Yiqing; Xie, Rongrong; Wang, Fengyun; Chen, Xiuli; Wu, Haiying; Zhang, Xiaohui; Zhang, Dandan; Yang, Bingyu; Fan, Qisang; Wang, Qing; et al. (Frontiers in Endocrinology, 2025)
BackgroundBrachydactyly type E (BDE) is characterized by variable shortening of metacarpals or metatarsals, often involving phalanges. It may occur as an isolated anomaly or as part of congenital syndromes. With advancements in molecular diagnostic technologies, how genetic testing enhances the precise diagnosis of BDE remains unclear. Our aims were to establish an algorithm for molecular genetic diagnostics in Chinese children with BDE and to explore the phenotype-genotype correlations of Chinese patients with BDE.MethodsWe reviewed left-hand wrist X-rays from children visiting Children’s Hospital of Soochow University (Jun 2021–Dec 2023). From 60,650 films, 135 BDE cases were identified, and their comprehensive phenotypes were collected. Whole-exome sequencing (WES) with copy number variation (CNV) analysis was performed on 60 patients and their parents. Sanger sequencing was used to validate single nucleotide variants (SNV) and indels.ResultsCausative variants were found in 19 patients. SNVs and indels affecting 10 genes were identified in 15 patients, and CNVs in four. GNAS mutations were the leading cause (four cases), followed by EXT1 and ACAN defects. The diagnostic yield was 19.1% in patients with isolated brachydactyly; 75% in patients with brachydactyly combined with short stature; 77.8% in patients with brachydactyly combined with facial dysmorphism; 83.3% in patients with brachydactyly combined with intellectual disability.ConclusionThrough comprehensive evaluation of genotype-phenotype correlations, we propose a diagnostic algorithm for precise molecular diagnosis in Chinese children with BDE.